A Survey of Antiprion Compounds Reveals the Prevalence of Non-PrP Molecular Targets - Poncet-Montange, Guillaume (American Society for Biochemistry and Molecular Biology, 2011)
Prion diseases are fatal neurodegenerative diseases caused by the accumulation of the misfolded isoform (PrP(Sc)) of the prion protein (PrP(C)). Cell-based screens have identified several compounds that induce a reduction in PrP(Sc) levels in infected cultured cells. However, the molecular targets of most antiprion compounds remain unknown. We undertook a large-scale, unbiased, cell-based screen for antiprion compounds and then investigated whether a representative subset of the active molecules had measurable affinity for PrP, increased the susceptibility of PrP(Sc) to proteolysis, or altered the cellular localization or expression level of PrP(C). None of the antiprion compounds showed in vitro affinity for PrP or had the ability to disaggregate PrP(Sc) in infected brain homogenates. These observations suggest that most antiprion compounds identified in cell-based screens deploy their activity via non-PrP targets in the cell. Our findings indicate that in comparison to PrP conformers themselves, proteins that play auxiliary roles in prion propagation may be more effective targets for future drug discovery efforts.